Optical spectroscopy for freshmen and secondary-school students - Buongiorno, Daniele; Michelini, Marisa (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
In the context of a experimental lab activity with freshmen in biotechnology and secondary school students, a study to monitor their reasoning about the interpretation of discrete atomic spectra was conducted. In the framework of the Model of Educational Reconstruction, the exploration of spontaneous interpretative models is an important step in the process of structuring educational proposals. Based on the existing research literature, we designed a study in which interpretative issues are problematized on the basis of phenomenology. The results of the subsequent data analysis regarding students’ reasoning points out that the microscopic interpretative models are useful to develop teaching proposals with the aim of obtaining a functional understanding about the formation of discrete spectra.